Climate change and health in Kuwait: temperature and mortality projections under different climatic scenarios - Barrak Alahmad; Ana Maria Vicedo-Cabrera; Kai Chen; Eric Garshick; Aaron S Bernstein; Joel Schwartz; Petros Koutrakis (Environmental Research Letters, 2022)
It is uncertain what climate change could bring to populations and countries in the hot desert environment of the Arabian Peninsula. Not only because they are already hot, countries in this region also have unique demographic profiles, with migrant populations potentially more vulnerable and constituting a large share of the population. In Kuwait, two-thirds of the population are migrant workers and record-high temperatures are already common. We quantified the temperature-related mortality burdens in Kuwait in the mid- (2050–2059) and end-century (2090–2099) decades under moderate (SSP2-4.5) and extreme (SSP5-8.5) climate change scenarios. We fitted time series distributed lag non-linear models to estimate the baseline temperature–mortality relationship which was then applied to future daily mean temperatures from the latest available climate models to estimate decadal temperature-mortality burdens under the two scenarios. By mid-century, the average temperature in Kuwait is predicted to increase by 1.80 °C (SSP2-4.5) to 2.57 °C (SSP5-8.5), compared to a 2000–2009 baseline. By the end of the century, we could see an increase of up to 5.54 °C. In a moderate scenario, climate change would increase heat-related mortality by 5.1% (95% empirical confidence intervals: 0.8, 9.3) by end-century, whereas an extreme scenario increases heat-related mortality by 11.7% (2.7, 19.0). Heat-related mortality for non-Kuwaiti migrant workers could increase by 15.1% (4.6, 22.8). For every 100 deaths in Kuwait, 13.6 (−3.6, 25.8) could be attributed to heat driven by climate change by the end of the century. Climate change induced warming, even under more optimistic mitigation scenarios, may markedly increase heat-related mortality in Kuwait. Those who are already vulnerable, like migrant workers, could borne a larger impact from climate change.